Radiolabeled iron oxide nanoparticles functionalized with PSMA/BN ligands for dual-targeting of prostate cancer - Bajwa, Danae Efremia; Salvanou, Evangelia-Alexandra; Theodosiou, Maria; Koutsikou, Theodora S.; Efthimiadou, Eleni K.; Bouziotis, Penelope; Liolios, Christos (Frontiers in Nuclear Medicine, 2023)
Prostate cancer (PCa) is the second most frequent cancer diagnosis in men and the fifth leading cause of death worldwide. Prostate Specific Membrane Antigen (PSMA) and Gastrin Releasing Peptide (GRP) receptors are overexpressed in PCa. In this study, we have developed a thin silica layer on the surface of iron oxide nanoparticles (IONs) with MPTES (carrying -SH groups, IONs-SH), which were then coupled either with a pharmacophore targeting PSMA (IONs-PSMA) or with bombesin peptide (IONs-BN), targeting GRP receptors, or with both (IONs-PSMA/BN). The functionalized IONs were characterized for their size, zeta potential, and efficiency of functionalization using dynamic light scattering (DLS) and Fourier-Transform Infrared Spectroscopy (FT-IR). All the aforementioned types of IONs were radiolabeled directly with Technetium-99m ( 99m Tc) and evaluated for their radiolabeling efficiency, stability, and binding ability on two different PCa cell lines (PC3 and LNCaP). The MTT assay demonstrated low toxicity of the IONs against PC3 and LNCaP cells, while the performed wound-healing assay further proved that these nanostructures did not affect cellular growth mechanisms. The observed hemolysis ratio after co-incubation with red blood cells was extremely low.Furthermore, the 99m Tc-radiolabeled IONs showed good stability in human serum, DTPA, and histidine, and high specific binding rates in cancer cells, supporting their future utilization as potential diagnostic tools for PCa with Single Photon Emission Computed Tomography (SPECT) imaging.